Effect of different 1-methylcyclopropene formulations and dosing on the ripening profile of Tommy Atkins mango fruits - Chomba, Geoffrey; Ambuko, Jane; Onyango, Cecilia; Ouko, John Robert (Frontiers in Horticulture, 2025)
Mango (Mangifera indica) is the second most economically important fruit in Kenya for local and export markets. Huge postharvest losses estimated between 30 to 50% characterize the mango value chain due to its climacteric nature and high perishability. These losses are exacerbated during ripening. However, the fruit’s shelf-life can be extended through the application of 1-Methylcyclopropene (1-MCP), an inhibitor of ethylene action. The efficacy of 1-MCP is affected by maturity at harvest, its formulation and concentration, and exposure time. This study sought to establish the effectiveness of the 1-MCP dosing range for the Tommy Atkins' mango variety harvested at two maturity stages defined subjectively based on shoulder elevation and objectively on flesh color as stage 1 (mature green) and stage 2 (advanced maturity). A homogeneous batch of 60 fruits from each maturity stage was exposed to two 1-MCP formulations (SmartFresh™–SmartTabs™ and SmartFresh™–Inbox Sachet). SmartFresh™–SmartTabs™ was applied at 0.5, 1.0, and 2.0 ppm concentrations for 12hrs and 24hrs while SmartFresh™–Inbox Sachet was applied at 0.5, 1.0, 2.0, and 4.0 ppm concentrations for 12hrs only. All treatment combinations were ripened at ambient conditions (25±3°C; 60±5% relative humidity). Samples of three fruits were taken at 3-day intervals for measurement of ethylene evolution, respiration rates, total soluble solids (TSS), color, and firmness. The 1-MCP response was significantly (P≤0.05) affected by maturity stage, 1-MCP treatment concentration, and exposure time. Untreated fruits exhibited higher ethylene peaks of 9.56 μL kg-1 h-1 and 13.29 μL kg-1 h-1 for stages 1 and 2 respectively. Stage 1 fruits subjected to 2.0ppm SmartFresh™–SmartTabs™ recorded a lower ethylene peak of 5.62 μL kg-1 h-1 and 3.62 μL kg-1 h-1 compared to fruits subjected to 1.0 ppm concentration, which recorded an ethylene peak of 5.95 μL kg-1 h-1 and 4.93 μL kg-1 h-1 for 12hrs and 24hrs respectively. Stage 2 fruits subjected to SmartFresh™–SmartTabs™ formulation, also delayed the ethylene peak with 2.0ppm recording ethylene peak of 6.55 μL kg-1 h-1 and 5.32 μL kg-1 h-1 compared to 1.0 ppm, which recorded 7.61 μL kg-1 h-1 and 7.15 μL kg-1 h-1 for 12hrs and 24hrs respectively. Stage 1 fruits subjected to SmartFresh™–Inbox Sachet at 4.0ppm lowered the ethylene peak to 3.89 μL kg-1 h-1. This concentration recorded the lowest peak compared to 5.54 µL kg-1 h-1, 5.12 μL kg-1 h-1, and 4.27 μL kg-1 h-1 for 0.5, 1.0, and 2.0ppm respectively. Interaction of 1-MCP concentration, exposure time, and maturity stage delayed other ripening-related changes including a decrease in hue angle, firmness, and increase in TSS. Results indicated that ripening was delayed by 1-MCP at an early stage of maturity; while the shelf life of treated fruits increased with increasing 1-MCP concentrations. SmartFresh™–SmartTabs™ applied at 2.0ppm for 24 hours achieved an increased shelf life of 12 days compared to the control in stage 1. SmartFresh™–Inbox Sachet applied at 2.0ppm and 4.0ppm significantly extended shelf life to 24 days and 21 days for stages 1 and 2 respectively. Overall, the findings of this study suggest that 2.0ppm of the ‘powder’ formulation and 4.0ppm of the ‘Inbox Sachet’ formulation of SmartFresh™ would offer optimal effects at 24hrs and 12hrs exposure respectively. We, therefore, wish to recommend these two formulations at the reported levels for commercial application in the Tommy Atkins' mango variety to prolong postharvest shelf life and maintain desirable quality attributes.